Health Literacy, Resilience and COVID-19 fear among Indonesian Survivors: Does age matter? - Daniswara Agusta Wijaya; Endang Widyorini; Margaretha Sih Setija Utami; Benedicta Audrey Putri Trisnadewi; Josephine Ferren Heryanto (Journal of Health and Behavioral Science, 2023)
Research on COVID-19 survivors is an emergent issue to be discussed since comprehensive knowledge needs to be obtained. Hence, an investigation of aspects related to health information management and psychological constructs among survivors is a necessity. The main objective of this study is to explore the relationship between health literacy, resilience, and COVID-19 fear among survivors. 245 COVID-19 survivors aged 14 to 67 years old (M=30.22; SD=12.707) completed the Health Literacy Scale, Brief Resilience Scale, and Fear of COVID-19 Scale in this study. Results of statistical analysis using PROCESS showed that among Indonesian survivors, resilience plays a full mediating role in the relationship between health literacy and COVID-19 fear. Furthermore, participants were then divided into three age groups. It was found that each age group presented different conditions regarding the relationships between those three variables. This study shows important findings about the importance of considering age in developing healthcare policy.